In-plane shear behaviour of stone masonry piers: a numerical study - A. A. Costa (2008)
This work aims to presenting a laboratory test of an existing Azorean stone masonry pier, transported to the Laboratory for Earthquake and Structural Engineering (LESE, FEUP, Porto), exhibiting significant energy dissipation but small displacement capacity. A complete 3D non-linear numerical simulation of the experimental test was also performed for simulating the observed response and good results were obtained, encouraging the use of this methodology either for calibration of other simplified models or in future works. After the first test, the pier was retrofitted with a strategy as used after the 1998 Azores earthquake and subsequently tested in order to assess that retrofitting efficiency and to evaluate the seismic resistance improvement. Indeed the major objective of that technique was achieved because a homogeneous and monolithic behaviour was observed, improving especially the displacement capacity of the pier.